Evidence of Judaism in Rough Cilicia and its Associations with Paganism - Durugönül, Serra; Mörel, Ahmet (Istanbuler Mitteilungen, 2024)
Abundant evidence for Jewish presence has been attested in the course of research in Rough Cilicia in recent years. The first category of evidence evaluated in this paper consists of epigraphic material from settlements such as Corycus, Diocaesarea and Seleucia; some of these inscriptions have been already published and are proven to have been associated with Jews, while the Jewish associations of twenty-one other inscriptions containing names of Jewish have not been previously recognized. Information in these inscriptions sheds light on the social and economic conditions of the Jews in the region. In addition to the epigraphic material, menorah reliefs indicating Jewish presence in the region are examined. A relief of a menorah carved next to a relief of Athena in the village of Sömek near Silifke (Seleucia) is noteworthy for it being placed next to a pagan symbol. Surveys in the region have brought to light the presence of similar menorahs and Pagan symbols at rural settlements such as in Örendibi near Sömek, Çaltıören, Köşkerli and Corycus. Altogether, these data illuminate the ways in which Jews lived together with Pagans and Christians and infl uenced each other culturally.